Design thinking : beyond the sticky notes - Lal, Devyani M. (Thousand Oaks : SAGE Publishing, 2021)
'What do some of the world's leading brands within design, technology and business industries have in common? They adopt and use the design thinking approach to address the challenges and steer the innovation process. While Silicon Valley experts have always been emulated for their unique thinking, the dynamic variables of Indian industry such as its competitive economy, evolving demographics, tastes and preferences prove that prescribed design thinking models may not effectively meet the solutions in unique real-world settings. Design Thinking: Beyond the Sticky Notes showcases how design practitioners in India like BYJU'S, Microsoft, Zoom, Rovio Entertainment, Google and Palantir Technologies have been breaking traditional notions of design practice in the domains of consumer technology and education. The book offers a glimpse at how these practitioners have been reinventing themselves with changing times and how design thinking tools and frameworks have evolved within their practice. Design thinking is not limited to a position, profession or specialization. It welcomes everyone'--
Bibliography : page [245]-248.
Keywords: Thought and thinking; Product design